Přesnost CT angiografie věnčitých tepen - Meijboom, W. Bob (Clinical Cardiology Alert, 2009)
This study sought to determine the diagnostic accuracy of 64-slice computed tomographic coronary angiography (CTCA) to detect or rule out significant coronary artery disease (CAD). BACKGROUND: CTCA is emerging as a noninvasive technique to detect coronary atherosclerosis. METHODS: We conducted a prospective, multicenter, multivendor study involving 360 symptomatic patients with acute and stable anginal syndromes who were between 50 and 70 years of age and were referred for diagnostic conventional coronary angiography (CCA) from September 2004 through June 2006. All patients underwent a nonenhanced calcium scan and a CTCA, which was compared with CCA. No patients or segments were excluded because of impaired image quality attributable to either coronary motion or calcifications. Patient-, vessel-, and segment-based sensitivities and specificities were calculated to detect or rule out significant CAD, defined as >or=50% lumen diameter reduction. RESULTS: The prevalence among patients of having at least 1 significant stenosis was 68%. In a patient-based analysis, the sensitivity for detecting patients with significant CAD was 99% (95% confidence interval [CI]: 98% to 100%), specificity was 64% (95% CI: 55% to 73%), positive predictive value was 86% (95% CI: 82% to 90%), and negative predictive value was 97% (95% CI: 94% to 100%). In a segment-based analysis, the sensitivity was 88% (95% CI: 85% to 91%), specificity was 90% (95% CI: 89% to 92%), positive predictive value was 47% (95% CI: 44% to 51%), and negative predictive value was 99% (95% CI: 98% to 99%). CONCLUSIONS: Among patients in whom a decision had already been made to obtain CCA, 64-slice CTCA was reliable for ruling out significant CAD in patients with stable and unstable anginal syndromes. A positive 64-slice CTCA scan often overestimates the severity of atherosclerotic obstructions and requires further testing to guide patient management.
Keywords: Confidence Intervals; Aged; senzitivita a specificita; lidé středního věku; senioři; Tomography, X-Ray Computed; lidé; Middle Aged; Prospective Studies; prospektivní studie; Coronary Artery Disease; nemoci koronárních tepen; interval spolehlivosti; Female; Predictive Value of Tests; koronární angiografie; financování organizované; Male; ženské pohlaví; Humans; Sensitivity and Specificity; mužské pohlaví; Coronary Angiography; Financing, Organized; počítačová rentgenová tomografie; prevalence; prediktivní hodnota testů; Prevalence